2015
DOI: 10.1002/cb.1521
|View full text |Cite
|
Sign up to set email alerts
|

Is Cinderella resurging? The impact of consumers' underdog disposition on brand preferences: Underdog brand biography and brand status as moderators

Abstract: This research attempts to explore the moderating roles of underdog brand biography and brand status in the impact of consumers' underdog disposition on brand preferences. A total of 218 on-the-job graduate students were randomly assigned to a 2 (explicitness of underdog brand biography: implicit vs. explicit) × 2 (brand status: emerging brands vs. established brands) factorial design. Results show that consumers with strong underdog disposition are likely to generate stronger brand preferences for established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 20 publications
3
51
0
Order By: Relevance
“…The underdog brand positioning does not focus on specific attributes, but rather stresses the underdog's humble background and noble, passionate, determined struggles. This positioning delivers symbolic benefits (Paharia et al, 2011;McGinnis et al, 2017), and the related positive effect is explained by the identity mechanism (McGinnis and Gentry, 2009;Paharia et al, 2011;Kao, 2015) grounded in the self-brand connection principle (Fournier, 1998;Aaker et al, 2004). Consumers support the underdog because its story reflects the underdog aspects of the consumers' own lives.…”
Section: Types Of Transgressions and Alignment With Brand Positioningmentioning
confidence: 99%
See 3 more Smart Citations
“…The underdog brand positioning does not focus on specific attributes, but rather stresses the underdog's humble background and noble, passionate, determined struggles. This positioning delivers symbolic benefits (Paharia et al, 2011;McGinnis et al, 2017), and the related positive effect is explained by the identity mechanism (McGinnis and Gentry, 2009;Paharia et al, 2011;Kao, 2015) grounded in the self-brand connection principle (Fournier, 1998;Aaker et al, 2004). Consumers support the underdog because its story reflects the underdog aspects of the consumers' own lives.…”
Section: Types Of Transgressions and Alignment With Brand Positioningmentioning
confidence: 99%
“…We contend that severely negative attitude changes are induced under autonomy-related (vs. community-related) ethical transgressions. This reasoning is based on consumers' basic supporting motivation toward the underdog brand (McGinnis and Gentry, 2009;Paharia et al, 2011;Kao, 2015). Identification with the underdog is the very mechanism that may explain the backfiring effect on the underdog positioning in the case of autonomy-related ethical transgressions.…”
Section: Do Ethical Transgressions Always Damage Underdog Brands?mentioning
confidence: 99%
See 2 more Smart Citations
“…() indicated the underdog effect is an underexplored area and an intriguing phenomenon in consumer research. Previous research has concluded that individuals prefer to connect themselves to winners and disconnect themselves from losers, implying that underdog brands are likely to be unfavorably evaluated (Kao, ). However, Paharia et al.…”
Section: Literature Reviewmentioning
confidence: 99%